Towards a tailored indoor horticulture: a functional genomics guided phenotypic approach. Issue 1 (December 2018) - Marondedze, Claudius; Liu, Xinyun; Huang, Shihui; Wong, Cynthia; Zhou, Xuan; Pan, Xutong; An, Huiting; Xu, Nuo; Tian, Xuechen; Wong, Aloysius
Abstract As indoor horticulture gathers momentum, electric (also termed artificial) lighting systems with the ability to generate specific and tunable wavelengths have been developed and applied. While the effects of light quality on plant growth and development have been studied, authoritative and reliable sets of light formulae tailored for the cultivation of economically important plants and plant traits are lacking as light qualities employed across laboratories are inconsistent. This is due, at least in part, to the lack of molecular data for plants examined under electric lights in indoor environments. It has hampered progress in the field of indoor horticulture, in particular, the transition from small-scale indoor farming to commercial plant factories. Here, we review the effects of light quality on model and crop plants studied from a physiological, physical and biochemical perspective, and explain how functional genomics can be employed in tandem to generate a wealth of molecular data specific for plants cultivated under indoor lighting. We also review the current state of lighting technologies in indoor horticulture specifically discussing how recent narrow-bandwidth lighting technologies can be tailored to cultivate economically valuable plant species and traits. Knowledge gained from a complementary phenotypic and functional genomics approach can be harvested not only for economical gains but also for sustainable food production. We believe that this review serves as a platform that guides future light-related plant research. Indoor horticulture: Lighting the way to sustainability Tailored multidisciplinary approaches to hone sustainable indoor horticulture could significantly improve plant yields and crop quality. Advances in artificial lighting systems could transform commercial-scale indoor horticulture, but the current technology is limited by a lack of molecular data for plants grown under such lighting schemes. Aloysius Wong at Wenzhou-Kean University in Wenzhou, China, and co-workers reviewed research into the effects of light quality and differing wavelengths on plant growth. The team advocate the use of plant type-specific and functional genomics studies to examine light-determined molecular traits and associated gene expression. These could be used to build an extensive catalog of light qualities that enhance indoor crop yields and quality. Combining LED lights of different colors and wavelengths shows promise, and the researchers highlight the potential of tunable narrow wavelength lights, such as lasers.